Dissemination of Portable Water Treatment for Providing Clean and Fresh Water for People Living in the Coastal Area of Meuraxa District, Banda Aceh - Darwin; Bulan, Ramayanty; Putra, Bambang Sukarno (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service aims to introduce and disseminate the portable water treatment that can be used for people living in the coastal area specifically in the Meuraxa District, Banda Aceh. Method: The implementation method of the Community Service Program activities uses descriptive analysis methods, demonstrations, and direct practice by group partners and community members. For the operation of the water treatment unit installation, community group partners will emphasize the demonstration method based on operational control by prioritizing operator safety. Practical Application: This integrated clean water treatment plant can desalinate water and separate organic and inorganic solid particles. This clean water treatment system is portable and has a working capacity of around ± 1000 liters. This installation is equipped with a sorting system and an automatic transfer system on the piping and pumping. This installation is needed to accelerate the process of cleaning and purifying water from brackish water to fresh water that is suitable for use and consumption. Conclusion: This product-based community service has produced a product in the form of a portable water treatment installation for filtering and cleaning water from pollutants, contaminants and/or impurities. Hence, this technology would help people living in the coastal area provide fresh water and clean water for their lives.